Primary perspectives : the acquisition of literacy in children in Ireland - a study exploring the views of primary school principals, teachers and children - Coyne, Angela (Trinity College (Dublin, Ireland). School of Education, 2016)
This research explores the views of teaching professionals: primary school principals, primary teachers, academics and children in relation to the acquisition of literacy in children in an Irish context. This study includes an online survey (162 responses) and research interviews (33) with teachers in different primary school settings in Ireland – rural, urban, schools designated as DEIS (Delivering Equal Opportunities in Schools) Band 1, Band 2, and Gaelscoileanna. This research also includes the views of children (115: third to sixth class, 9–12 years) obtained in research questionnaires. This study identifies the most influential factors in children’s literacy acquisition from the perspectives of teaching professionals in this research. These factors relate to parental and family context and involvement, the influence of language, culture and socio-economic factors. Research findings convey that factors occur simultaneously and are interrelated; an important consideration in establishing an appreciation of the potential opportunities and challenges presented in the current context and in addressing implications for best practice. This study identifies a number of relevant challenges relating to pupil attitudes and abilities and the support available to children at home and at school. In addition, this research outlines some important considerations for the future in addressing the literacy needs of children in an Irish context. These relate to school and curricular considerations and pupil specific considerations. Research findings emphasise the importance of teacher education, a whole school approach to literacy acquisition and the availability of appropriate educational resources. In addition, findings reiterate the need for effective curricular implementation in oral language, reading and writing and the benefits of cross-curricular integration. Furthermore, this research acknowledges the importance of parental involvement in influencing children’s literacy acquisition, the need to encourage positive pupil attitudes towards learning in literacy and the importance of appropriate differentiation in the teaching of children of both genders and different abilities. Overall, similar views were expressed by teaching professionals and children in this research, in relation to many issues, and in most instances, findings were in keeping with those reported in recent research literature. Similar views were expressed by teaching professionals and children regarding the need for opportunities to improve oral language, pronunciation and comprehension. In addition, research findings suggest that teaching professionals and children recognised that literacy can influence personal development and acknowledged the associations between literacy and life-long learning. While findings from this research provide the potential for further exploration and discussion, a knowledge and awareness of the influential factors, challenges and considerations for the future in addressing literacy is of benefit to educators in their endeavours to promote and facilitate children’s literacy acquisition in different educational contexts.
Keywords: Education, Ph.D.; Ph.D. Trinity College Dublin